A Literature Review: Acute Pharyngitis and Laryngitis - Ningrum, Sania Tresna; Hardian, Excell Defry; Fawaiz, Afdhila Anugerah; Ramdhini, Tisya Nasywa (Jurnal Biologi Tropis, 2025)
Acute pharyngitis and laryngitis refer to inflammation of the pharynx and larynx. These illnesses are typically brought on by bacterial or viral infections. Reflux, cancer, allergies, trauma, and poisoning are other less frequent causes. The literature review aims to obtain information related to acute pharyngitis and laryngitis. The method used is systematic literature. The results of the literature review obtained that the pathogen most often causing acute pharyngitis is beta-hemolytic Streptococcus group A. Common symptoms of pharyngitis are a sore or painful throat, an itchy throat, and fever. Acute laryngitis is inflammation that occurs in the larynx area, and its etiology can be divided into two: infectious and non-infectious. The most common pathogens causing acute laryngitis are rhinovirus, parainfluenza virus, Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. These pathogens cause symptoms of acute laryngitis such as difficulty swallowing, persistent fever, severe sore throat, coughing up blood, and difficulty breathing. Since the majority of cases have a bacterial origin, the use of antibiotics is the basic management in cases of acute pharyngitis and laryngitis.